Molecular imaging in drug development - Willmann, Jürgen K.; van Bruggen, Nicholas; Dinkelborg, Ludger M.; Gambhir, Sanjiv S. (Nature reviews. Drug discovery, 2008)
Key Points Drug development is a costly, time-intensive and high-risk endeavour, with only two to three approvals for novel therapeutics in new drug classes per year eventually making it to market. New strategies are required to identify promising new drug candidates early on and, likewise, to terminate those candidates that are unlikely to be successful, thus allowing a more rapid and efficient move to pivotal trials. Molecular imaging attempts to characterize and quantify biological processes at the cellular and subcellular level in intact living subjects. It exploits specific molecular probes and intrinsic tissue characteristics as the source of image contrast, providing the potential for understanding of integrative biology, earlier detection and characterization of disease, and evaluation of treatment. As most molecular imaging techniques are routine in clinical radiology departments and have counterparts in the experimental research setting, it is possible to design preclinical experiments that not only predict clinical imaging observations but also provide a mechanistic understanding of the observed biological response. Molecular imaging has the potential to have a significant impact on different phases of drug development, including target expression, compound screening and optimization, as well as Phases I to III clinical studies. Examples are detailed in the text of the article. The option of an exploratory IND (eIND) initiated by the US Food and Drug Administration enables first-in-human molecular imaging studies to be performed with reduced preclinical support as compared to that required for a full IND. Consortia such as the Alzheimer's Disease Neuroimaging Initiative, the American College of Radiology Imaging Network and the High-Risk Plaque Initiative seek to correlate a number of imaging biomarkers with the clinical manifestations of diseases and, if successful, will greatly increase the inclusion of these imaging techniques in exploratory clinical development of novel therapeutics. Molecular imaging, which can allow the non-invasive monitoring of biological processes in living subjects, has the potential to enhance understanding of disease and drug activity in both preclinical and clinical drug studies, aiding effective translational research. Gambhir and colleagues review the applications of molecular imaging in drug development, and discuss challenges that need to be addressed to optimize its utility. Molecular imaging can allow the non-invasive assessment of biological and biochemical processes in living subjects. Such technologies therefore have the potential to enhance our understanding of disease and drug activity during preclinical and clinical drug development, which could aid decisions to select candidates that seem most likely to be successful or to halt the development of drugs that seem likely to ultimately fail. Here, with an emphasis on oncology, we review the applications of molecular imaging in drug development, highlighting successes and identifying key challenges that need to be addressed for successful integration of molecular imaging into the drug development process.